Characterisation of carbon paste electrodes for real-time amperometric monitoring of brain tissue oxygen. - Bolger, F; McHugh, S; Bennett, R; Li, J; Ishiwari, K; Francois, J; Conway, M; Gilmour, G; Bannerman, D; Fillenz, M; Tricklebank, M; Lowry, J (2011)
Tissue O₂ can be monitored using a variety of electrochemical techniques and electrodes. In vitro and in vivo characterisation studies for O₂ reduction at carbon paste electrodes (CPEs) using constant potential amperometry (CPA) are presented. Cyclic voltammetry indicated that an applied potential of -650 mV is required for O₂ reduction at CPEs. High sensitivity (-1.49 ± 0.01 nA/μM), low detection limit (ca. 0.1 μM) and good linear response characteristics (R² > 0.99) were observed in calibration experiments performed at this potential. There was also no effect of pH, temperature, and ion changes, and no dependence upon flow/fluid convection (stirring). Several compounds (e.g. dopamine and its metabolites) present in brain extracellular fluid were tested at physiological concentrations and shown not to interfere with the CPA O₂ signal. In vivo experiments confirmed a sub-second response time observed in vitro and demonstrated long-term stability extending over twelve weeks, with minimal O₂ consumption (ca. 1 nmol/h). These results indicate that CPEs operating amperometrically at a constant potential of -650 mV (vs. SCE) can be used reliably to continuously monitor brain extracellular tissue O₂.